PERAN KOMUNIKASI KELOMPOK PADA KOMUNITAS BATIK SIDO ASIH DI MASA PANDEMI COVID-19 - Retno Dyah Kusumastuti; Airlangga Surya Kusuma (Jurnal Pustaka Komunikasi, 2023)
The existence of the Covid-19 pandemic has hit the tourism sector hard, including tourist villages, where many tourist villages have been closed and do not accept tourist visits. One of these tourist villages is Giriloyo Tourism Village, where the closure of this tourist village has hit the economy of the batik craftsmen who are members of the Sido Asih Batik Community. The purpose of this study is to describe and explain the role of group communication in the Sido Asih Batik Community in dealing with the impact of the Covid-19 pandemic. The research method used is descriptive qualitative with a case study approach. Data collection techniques used in this study were observation, interviews, and literature review. This study shows that the role of group communication is important, because group communication can act as a medium for community coordination and consolidation. Due to the pandemic, group communication is carried out virtually via the WhatsApp (WA) group. Group communication is also used as a forum for joint problem solving and produces a number of initiatives, such as selling batik cloth online using WhatsApp (WA) to a number of cities in Indonesia, and selling other products such as herbal medicine. Another role of group communication is to strengthen each other and work together in dealing with the Covid-19 pandemic through traditions such as jimpitan, as well as a medium for making certain decisions, such as the decision to reopen the Giriloyo Tourism Village.